2020
DOI: 10.1093/mnras/staa758
|View full text |Cite
|
Sign up to set email alerts
|

Interarm islands in the Milky Way – the one near the Cygnus spiral arm

Abstract: This study extends to the structure of the Galaxy. Our main goal is to focus on the first spiral arm beyond the Perseus arm, often called the Cygnus arm or the 'Outer Norma' arm, by appraising the distributions of the masers near the Cygnus arm. The method is to employ masers whose trigonometric distances were measured with accuracy. The maser data come from published literaturesee column 8 in Table 1 here, having been obtained via the existing networks ( US VLBA , the Japanese VERA, the European VLBI, and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…With NIR deep imaging, we identified one cluster in each region, having 73 and 89 cluster members in S207 and S208, respectively, with a mass detection limit of 0.1 M ⊙ for S207 and ∼0.2 M ⊙ for S208. From the K-band luminosity function (KLF) fitting of the clusters, S207 and S208 are likely to be located at D = 4 kpc from the Sun, which suggests that two regions are located in the interarm region between the Cygnus and Perseus arms (Vallée 2020). The fitting also suggested that S207 is at the end of the embedded cluster phase (∼2-3 Myr), while the S208 cluster is very young (∼0.5 Myr).…”
Section: Introductionmentioning
confidence: 95%
“…With NIR deep imaging, we identified one cluster in each region, having 73 and 89 cluster members in S207 and S208, respectively, with a mass detection limit of 0.1 M ⊙ for S207 and ∼0.2 M ⊙ for S208. From the K-band luminosity function (KLF) fitting of the clusters, S207 and S208 are likely to be located at D = 4 kpc from the Sun, which suggests that two regions are located in the interarm region between the Cygnus and Perseus arms (Vallée 2020). The fitting also suggested that S207 is at the end of the embedded cluster phase (∼2-3 Myr), while the S208 cluster is very young (∼0.5 Myr).…”
Section: Introductionmentioning
confidence: 95%
“…The question of the possible bending of the Perseus arm is mentioned (Section 4 in [26] suggested 2 arms; in contrario, [27] suggested an interarm island near the Perseus arm). Also,the width of each spiral arm is thus not well defined in Gaia DR3; in contrario, a new multi-tracer approach for defining the spiral arm width was advocated (masers near the Shock front/inner arm versus broad diffuse broad CO gas near the Potential Minimum/outer arm -see [28]).…”
Section: Locations Of Spiral Arms -Complementarity Of Arm Tangents Wi...mentioning
confidence: 99%
“…The Sun is located in an interarm, in between two long spiral arms (Sagittarius arm and Perseus arm). Other small interarm islands are known within our Galactic disk (Vallée 2018;Vallée 2020). The magnetic field strength there is not known (too few data).…”
Section: Turbulence Local and Everywherementioning
confidence: 93%